2014
DOI: 10.1080/08870446.2014.893345
|View full text |Cite
|
Sign up to set email alerts
|

‘See it doesn’t look pretty does it?’ Young adults’ airbrushed drinking practices on Facebook

Abstract: A range of negative health outcomes are associated with young adults' drinking practices. One key arena where images of, and interaction about, drinking practices occurs is social networking sites, particularly Facebook. This study investigated the ways in which young adults' talked about and understood their uses of Facebook within their drinking practices. Face-to-face, semi-structured interviews were conducted with seven New Zealand young adults as they displayed, navigated and talked about their Facebook p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(131 citation statements)
references
References 54 publications
7
116
2
2
Order By: Relevance
“…Nevertheless, that participants were most exposed to user-created alcohol promotion on social networking websites supports why such content has featured prominently in exploratory content research (Atkinson et al, 2014;Fournier & Clarke, 2011), experimental studies (Litt & Stock, 2011), longitudinal surveys (Boyle et al, 2016), and qualitative research (Lyons et al, 2014). That the reported awareness of, and participation with, user-created alcohol promotion on social networking websites was higher than previous surveys (e.g.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Nevertheless, that participants were most exposed to user-created alcohol promotion on social networking websites supports why such content has featured prominently in exploratory content research (Atkinson et al, 2014;Fournier & Clarke, 2011), experimental studies (Litt & Stock, 2011), longitudinal surveys (Boyle et al, 2016), and qualitative research (Lyons et al, 2014). That the reported awareness of, and participation with, user-created alcohol promotion on social networking websites was higher than previous surveys (e.g.…”
Section: Discussioncontrasting
confidence: 45%
“…Research has also suggested that young adults do not always recognise commercial alcohol marketing (Lyons et al, 2014;Niland, McCreanor, Lyons, & Griffin, 2017). Given the close and interacting relationship between the two (Figure 1) it is therefore possible some participants may have unintentionally reported exposure to content they assumed to be user-created alcohol promotion without recognising that it was in fact commercial marketing (e.g.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gap between young men's and women's experiences of drinking and intoxication has begun to narrow as women have become more active participants in night life drinking spaces, and as a result, more women are reporting drinking and drunkenness (Atkinson et al, 2012b;Fuller, 2015;Hibell et al, act as sites of control for women and as contexts in which gender and classed restrictions continue to be being placed upon them (Atkinson et al, 2012a;Bailey et al, 2015;Griffin et al, 2009Nicholls, 2016;Niland et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of urban night-time activities is dominated by a strong emphasis on alcohol and drug use (Wilton and Moreno, 2012), including the nightliferelated online activities. A growing scholarship is concerned with the "intoxigenic digital spaces" (Griffiths and Casswell, 2010:525) produced through ICTs (Griffiths and Casswell, 2010;Brown and Gregg, 2012;Niland et al, 2014;Lyons et al, 2017); it draws on the "pathologizing of alcohol consumption" (Jayne et al, 2008:249) and predominant understandings of young people as vulnerable and in need of protection (Valentine, 1996;Aitken, 2001). Through the lens of Ahmed's phenomenological reading and reflections on orientation, I have found that young people orientate themselves in much broader ways towards ICTs.…”
Section: Resultsmentioning
confidence: 99%